Understanding the Educational Attainment Polygenic Index and Its Interactions with SES in Determining Health in Young Adulthood - Atticus Bolyard; Peter A. Savelyev (Institute of Labor Economics (IZA), 2024)
Based on the sample of The National Longitudinal Study of Adolescent to Adult Health (Add Health), we investigate the formation of health capital and the role played by genetic endowments, parental SES, and education. To measure genetic endowments we take advantage of the new availability of quality polygenic indexes (PGIs), which are optimally-weighted summaries of individual molecular genetic data. Our main focus is on the Educational Attainment Polygenic Index (EA PGI), which is designed to predict the highest level of education achieved in life. We find that the EA PGI demonstrates stronger effects on health and health behaviors for subjects with high parental socioeconomic status (SES). These effects are only partially explained by education as a mechanism. We provide suggestive evidence for the mechanisms behind estimated relationships, including early health, skills, and the parents' and child's own attitudes towards education, as well as outcomes related to occupation and wealth. We also show that a strong association between education and health survives controlling for a large set of PGIs that proxy health, skills, and home environment, with only a modest reduction in regression coefficients despite controlling for major expected confounders. This result informs the ongoing debate about the causal relationship between education and health and the confounders behind the education-health gradient.
Keywords: I12; I14; I24; J24; 330; health; health behaviors; Polygenic Index (PGI); Polygenic Score (PGS); Educational Attainment; parental socioeconomic status (SES); child development; education; mediators; Add Health data